2021
DOI: 10.3390/membranes11020086
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Functionalized Graphene Oxide as Membrane Nanofiller: Spectral and Structural Studies

Abstract: High-degree functionalization of graphene oxide (GO) nanoparticles (NPs) using polydopamine (PDA) was conducted to produce polydopamine functionalized graphene oxide nanoparticles (GO-PDA NPs). Aiming to explore their potential use as nanofiller in membrane separation processes, the spectral and structural properties of GO-PDA NPs were comprehensively analyzed. GO NPs were first prepared by the oxidation of graphite via a modified Hummers method. The obtained GO NPs were then functionalized with PDA using a GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…This study mainly studied the adsorption of GO by iron tailings in different solution pH (5,6,7,8,9,10), the mass of iron tailings (30 mg, 40 mg, 50 mg, 60 mg, 70 mg) and the adsorption effect of GO at initial concentrations (40 mg/L, 60 mg/L, 80 mg/L, 100 mg/L) and temperatures (298.15 K, 303.15 K, 313.15 K) and the corresponding adsorption isotherm model, adsorption thermodynamic model and adsorption kinetic model were obtained by fitting the test data.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study mainly studied the adsorption of GO by iron tailings in different solution pH (5,6,7,8,9,10), the mass of iron tailings (30 mg, 40 mg, 50 mg, 60 mg, 70 mg) and the adsorption effect of GO at initial concentrations (40 mg/L, 60 mg/L, 80 mg/L, 100 mg/L) and temperatures (298.15 K, 303.15 K, 313.15 K) and the corresponding adsorption isotherm model, adsorption thermodynamic model and adsorption kinetic model were obtained by fitting the test data.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…In recent years, graphene has strong application prospects in many scientific fields due to its unique electrical, optical, mechanical and other properties and has received extensive attention from many scholars [1][2][3][4]. Graphene oxide (GO) is a derivative of graphene, it is usually synthesized from pure graphite powder by modified Hummers method [5]. It is easy to manufacture, low in cost, rich in oxygen-containing functional groups, has a high specific surface area [6], and is easily dispersed stably in solvents [7].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies were considered in this Special Issue. The first one is by Alkhouzaam et al [ 5 ] who produced Graphene oxide nanoparticles using the modified Hummer’s method. The obtained GO NP were amine functionalized using the bio-inspired polydopamine (PDA) to increase their hydrophilicity, dispersibility in aqueous and organic solvents, antibacterial properties, surface area, adsorption capacity, mechanical and thermal stability [ 6 , 7 ].…”
mentioning
confidence: 99%
“…However, all membranes retained their desalination capabilities despite the addition of the activated carbon. Alkhouzaam et al [39] presented Recent work using fabricated polystyrene membranes along with a novel, activated carbon-doped, electrospun, polystyrene membrane was done by Abdelrazeq et al [37] and Esteves et al [38] to tackle produced water treatment using a bench-scale direct-contact membrane distillation (DCMD) bench-scale unit. Results have shown that membranes including activated carbon-doped layers showed a 20× greater specific surface area as compared to undoped membranes.…”
mentioning
confidence: 99%
“…However, all membranes retained their desalination capabilities despite the addition of the activated carbon. Alkhouzaam et al [39] presented another interesting study where polydopamine functionalized graphene oxide nanoparticles (GO-PDA NPs) were prepared to investigate their structural properties in membrane separation processes. The hydrophilicity was significantly improved despite the low concentrations of GO-PDA layer (1 wt.%) on the PS substrate.…”
mentioning
confidence: 99%